Bimetal‐Organic‐Framework Derivation of Ball‐Cactus‐Like Ni‐Sn‐P@C‐CNT as Long‐Cycle Anode for Lithium Ion Battery - Dai, Ruoling; Sun, Weiwei; Lv, Li‐Ping; Wu, Minghong; Liu, Hao; Wang, Guoxiu; Wang, Yong (Small (Weinheim an der Bergstrasse, Germany), 2017)
Metal phosphides are a new class of potential high‐capacity anodes for lithium ion batteries, but their short cycle life is the critical problem to hinder its practical application. A unique ball‐cactus‐like microsphere of carbon coated NiP2/Ni3Sn4 with deep‐rooted carbon nanotubes (Ni‐Sn‐P@C‐CNT) is demonstrated in this work to solve this problem. Bimetal‐organic‐frameworks (BMOFs, Ni‐Sn‐BTC, BTC refers to 1,3,5‐benzenetricarboxylic acid) are formed by a two‐step uniform microwave‐assisted irradiation approach and used as the precursor to grow Ni‐Sn@C‐CNT, Ni‐Sn‐P@C‐CNT, yolk–shell Ni‐Sn@C, and Ni‐Sn‐P@C. The uniform carbon overlayer is formed by the decomposition of organic ligands from MOFs and small CNTs are deeply rooted in Ni‐Sn‐P@C microsphere due to the in situ catalysis effect of Ni‐Sn. Among these potential anode materials, the Ni‐Sn‐P@C‐CNT is found to be a promising anode with best electrochemical properties. It exhibits a large reversible capacity of 704 mA h g−1 after 200 cycles at 100 mA g−1 and excellent high‐rate cycling performance (a stable capacity of 504 mA h g−1 retained after 800 cycles at 1 A g−1). These good electrochemical properties are mainly ascribed to the unique 3D mesoporous structure design along with dual active components showing synergistic electrochemical activity within different voltage windows. Bimetal‐organic frameworks of a Ni‐Sn‐BTC metal organic framework precursor are used to synthesize a unique ball‐cactus‐like Ni‐Sn‐P@C‐CNT microsphere with carbon overlayer and deep‐rooted CNTs. It delivers a large Li‐storage capacity of 704 mA h g−1 after 200 cycles at 100 mA g−1 and excellent high‐rate cycling performance. A capacity of 504 mA h g−1 is retained after 800 cycles at 1 A g−1.